Conservation agriculture in maize-legume farming systems in Southern Africa: IPSR Innovation Profile - Thierfelder, Christian L.; Nyagumbo, Isaiah (2022)
Conservation Agriculture (CA) is based on three key principles: minimum soil disturbance, provision of permanent soil cover and the use of rotations or associations amongst other good agriculture practices. These CA principles are applicable to a wide range of crop production systems from low-yielding, rainfed conditions to high-yielding, irrigated conditions. However, the techniques used may vary from place to place depending on farm power, system management conditions and farmer circumstances. CA aims at rebuilding the soil, optimizing crop production inputs especially labour, and increasing profits. The social and economic benefits gained from combining production and protecting the environment under CA, including reduced input and labour costs, are greater than those from production alone. With CA, farming communities become providers of more healthy living environments for the wider community through reduced use of fossil fuels and through conservation of environmental integrity and services. CA in maize-legume systems addresses major production challenges in farming areas of Eastern and Southern Africa where both cereals and legumes are commonly grown.